I A - TOPAR ELEMENTLERIN OQÍTÍWDA KLASTER METODÍNAN PAYDALANÍW - Aymurzaeva, L.; Aytbaeva, H.; Kudaybergenova, A. (SCIENCE and SOCIETY, 2025)
The article discusses the use of the Cluster method in teaching elements of group I A in chemistry lessons. In class activities, this method is considered as a set of ideas expressed by students and increases students' creativity and activity.